Bradykinin-induced sensitization of transient receptor potential channel melastatin 3 calcium responses in mouse nociceptive neurons - Behrendt, Marc; Solinski, Hans Jürgen; Schmelz, Martin; Carr, Richard (Frontiers in cellular neuroscience, 2022)
TRPM3 is a calcium-permeable cation channel expressed in a range of sensory neurons that can be activated by heat and the endogenous steroid pregnenolone sulfate (PS). During inflammation, the expression and function of TRPM3 are both augmented in somatosensory nociceptors. However, in isolated dorsal root ganglion (DRG) neurons application of inflammatory mediators like prostaglandins and bradykinin (BK) inhibit TRPM3. Therefore, the aim of this study was to examine the effect of preceding activation of cultured 1 day old mouse DRG neurons by the inflammatory mediator BK on TRPM3-mediated calcium responses. Calcium signals were recorded using the intensity-based dye Fluo-8. We found that TRPM3-mediated calcium responses to PS were enhanced by preceding application of BK in cells that responded to BK with a calcium signal, indicating BK receptor (BKR) expression. The majority of cells that co-expressed TRPM3 and BKRs also expressed TRPV1, however, only a small fraction co-expressed TRPA1, identified by calcium responses to capsaicin and supercinnamaldehyde, respectively. Signaling and trafficking pathways responsible for sensitization of TRPM3 following BK were characterized using inhibitors of second messenger signaling cascades and exocytosis. Pharmacological blockade of protein kinase C, calcium-calmodulin-dependent protein kinase II and diacylglycerol (DAG) lipase did not affect BK-induced sensitization, but inhibition of DAG kinase did. In addition, release of calcium from intracellular stores using thapsigargin also resulted in TRPM3 sensitization. Finally, BK did not sensitize TRPM3 in the presence of exocytosis inhibitors. Collectively, we show that preceding activation of DRG neurons by BK sensitized TRPM3-mediated calcium responses to PS. Our results indicate that BKR-mediated activation of intracellular signaling pathways comprising DAG kinase, calcium and exocytosis may contribute to TRPM3 sensitization during inflammation.
Gesehen am 30.06.2022